Development of Thematic Skill Learning Based on the 21th Century Skill Model for Fourth Graders - Satria, Tio Gusti; Hajani, Tri Juli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
Thematic learning using 21st Century skills is learning with higher-order thinking skills (HOTS). It is a series of stages of activities organized in such a way that students can master the competencies that must be achieved in thematic learning by actively participating. This research is educational research with a design research model that develops a product. The product developed in this study is a thematic lesson plan for grade IV elementary school. Thematic learning implementation plan based on 21st Century skills models with an overall validation yield of 92% (very valid). The thematic learning media is very practical with an average of 92.5%. The effectiveness of the use of thematic lesson plans can be known through the learning activities of students while learning by using this learning tool is very effective, and students' learning outcomes are above the school minimum completeness criteria. These observations illustrate that the use of thematic lesson plans based on 21st Century skills models have been effectively implemented.